Download presentation

Presentation is loading. Please wait.

Published byJoanna Stokes Modified over 8 years ago

1
1245712457 2 Objective - To graph linear equations using x-y charts. One Variable Equations Two Variable Equations 2x - 3 = 11 +3 2x = 14 x = 7 One Solution Two Solutions x + y = 5 Solutions: x = 1, y = 4 x = 2, y = 3 x = 4, y = 1 x = 5, y = 0 x = 7, y = -2 Ordered Pairs (x,y) (1,4) (2,3) (4,1) (5,0) (7,-2) x y 4 3 1 0 -2 Infinite Solutions

2
Determine whether the ordered pair is a solution to the given equation. Not a solution It is a solution It is a solution Not a solution ? ? ? ?

3
State whether the given point is a solution to 3x - y = 5. 1) (2, 1) 2) (4, 5) 3) (-3, -14) 4) 5) (-1, 2) 3(2) - 1 = 5 Yes 3(4) - 5 = 5 No 3(-3) - -14 = 5 Yes 3(-1) - 2 = 5 No

4
Complete the chart and graph. y = 2x - 3 xy -3 -2 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 1 3 x y

5
x y Complete the chart and graph. y = 2x - 3 xy -3 -2 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 1 3

6
x y Complete the chart and graph. y = 2x - 3 xy -3 -2 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 1 3

7
x y Complete the chart and graph. y = 2x - 3 xy -3 -2 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 1 3

8
x y Complete the chart and graph. y = 2x - 3 xy -3 -2 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 1 3

9
x y Complete the chart and graph. y = 2x - 3 xy -3 -2 0 1 2 3 2(-3) - 3 = -9 2(-2) - 3 = -7 -5 -3 1 3 This line represents all real solutions to y = 2x - 3.

10
1) 2x + y = 5 2) -x + 2y = -4 -2x y = -2x + 5 +x 2y = x - 4 2 Solve the following equations for y. (Function Form)

11
3) 3x + 5y = 10 4) -2x + 3y = -6 -3x 5y = -3x + 10 5 +2x 3y = 2x - 6 3 Solve the following equations for y. (Function Form)

12
x y Solve the equation for y, complete the chart, and graph. 1) 3x + 2y = 4 -3x 2y = -3x + 4 2 xy -4 -2 0 2 4 6 8 5 2 -4 -7

13
x y 2) x - 3y = 6 -x -3y = -x + 6 -3 xy -6 -3 0 3 6 9 -4 -3 -2 0 1 Solve the equation for y, complete the chart, and graph.

14
x y Solve the equation for y, find at least five solutions, and graph. 3) x + 2y = 8 -x 2y = -x + 8 2 xy -4 -2 0 2 4 6 6 5 4 3 2 1

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google